- - Krstić Mistridželović, Ivana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: The paper analyzes the policy of the Delegation of the Kingdom of SCS at the Peace Conference in Versailles in respect of Vojvodina, which was incorporated into the Kingdom of Serbia by the decision of the Grand National Assembly in Novi Sad dated November 25, 1918, and joined the newly formed Kingdom of Serbs, Croats and Slovenes. The introductory part of the paper summarizes issues important for the work of the Delegation in territorial matters. External factors that posed an objective threat to the Delegation's policy regarding Vojvodina were analyzed afterwards. The paper further discusses internal factors that disturbed the construction of the unique views of the Yugoslav Delegation in Versailles against Vojvodina. Different concepts on the borders of the Yugoslav state in the Delegation and the work of the Ethnographic Section which was especially significant in determining the territory of Vojvodina and demarcation with neighboring countries were both analyzed. On the basis of these analyzes in the final discussions were given some specific conclusions, as well as an a general assessment of the work of the Delegation of the Kingdom of SCS in Versailles regarding Vojvodina was given.